Grain Size Distribution on a Forged Ni-Cr-Mo Low-Alloy Steel - Quintana Hernández, María José; Ales, T.; Gonzalez-Ojeda, Roberto; Collins, P.; Kenney, M. (My University, 2018)
Microalloyed Ni-Cr-Mo steel (8620) combines good characteristics of formability during forging at 1100°C with the capacity to transform into martensite, while distributing residual stresses and allowing surface treatments and modifications in mechanical parts such as gears and cams. The work presents grain size measurements at different locations of a hot forged gear analyzing it by quantitative metallography techniques and simulating deformation by finite element modeling to estimate local strain and strain rate. Dynamic recrystallization mathematical models for the austenitic initial grain size before forging were applied to calculate theoretical final grain size and correlate the results with microstructural observations, taking also into account the role of precipitation of Cr and Mo carbides. Copyright © 2018 MS&T18®

Microalloyed Ni-Cr-Mo steel (8620) combines good characteristics of formability during forging at 1100°C with the capacity to transform into martensite, while distributing residual stresses and allowing surface treatments and modifications in mechanical parts such as gears and cams. The work presents grain size measurements at different locations of a hot forged gear analyzing it by quantitative metallography techniques and simulating deformation by finite element modeling to estimate local strain and strain rate. Dynamic recrystallization mathematical models for the austenitic initial grain size before forging were applied to calculate theoretical final grain size and correlate the results with microstructural observations, taking also into account the role of precipitation of Cr and Mo carbides. Copyright © 2018 MS&T18®